Penentuan Nilai SPF Krim Tabir Surya Berbasis Minyak Biji Anggur - Wahyuni P (Herbal Medicine Journal, 2018)
Sunscreen is a cosmetic product that is used on the surface of the skin that works, among others, by absorbing, scattering, or reflecting ultraviolet light. Grape seed oil is a vegetable oil that is rich in vitamin E which acts as an antioxidant and absorbs UV light at wavelengths of 280-320 nm. The purpose of this study was to determine the effect of grape seed oil concentration on SPF values ​​from sunscreen lotion preparations. The sunscreen lotion is made in 5 formulas namely Formula 1 (lotion base), Formula 2 (positive control base), Formula 3 (5% grape seed oil), Formula 4 (10% grape seed oil) and Formula 5 (grapeseed oil) 15%), where Formula 2 to Formula 5 is added with oxybenzone (2%) and octyl methoxycinamate (5%). Determination of SPF value was carried out by Uv-Vis spectrophotometric method. The results showed that the SPF results showed that the higher the concentration of grape seed oil, the higher the SPF value produced. The Formula 1 SPF value is 0.06, Formula 2 is 11.90, Formula 3 is 12.38, Formula 4 is 12.81 and Formula 5 is 13.14. From the results of this study, it was concluded that the addition of various concentrations of grapeseed oil can increase the value of SPF and have good quality.